On polar lows and their formation - Stoll, Patrick Johannes (Quarterly Journal of the Royal Meteorological Society, 2020)
Polar lows are small, but extreme cyclones that develop in marine polar air mass. They feature one of the largest natural hazards in the polar regions. Their associated strong winds, high waves, substantial amounts of snow fall, low visibility and possibility for ice accumulation on ships and airplanes cause threats for coastal communities and marine operations. Hence, accurate prediction of polar lows is of major importance. This, however, is a challenge for meteorological services due to the fast, non-linear development of these cyclones. The evaluation of weather-prediction models for polar-low situations is difficult, since polar lows appear in a large variety and the scientific community has not yet accepted a singular conceptual model describing their development. Further, a consistent global investigation of polar lows has not yet been performed. In this thesis, the formation of polar lows is investigated. The aforementioned issues are targeted. In order to compare the polar-low activity across ocean basins, the first global dataset of polar lows is derived (Paper I). For the derivation of the dataset, the characteristics of polar lows are compared to other storms. Most polar-low activity is found in the North-East Atlantic, namely the Nordic Seas and the Denmark Strait. The number of very intense polar lows was declining during the recent 40 years. This thesis evaluates two modern weather-prediction models in forecasting a well-observed polar-low case (Paper I, II). Both models capture the polar low reasonably well for the analysis time, but show considerable issues at forecast times of more than one day. The polar low appears very sensible to the sea-surface temperature. Additionally, the variety of polar lows is examined (Paper I, III). An earlier proposed classification scheme into forward and reverse-shear cases is extended by adding left and right-shear systems to the scheme. Polar lows in all four shear categories are characterised by a baroclinc cyclogenesis. In conclusion, this thesis supports ...